Are Large Shareholders Willing to Pay Top Executives Equity-Based Compensation in China? The Moderating Role of Female Executives - Zheng, ZHANG Chang-; Fang, GENG Jian-; Yue, ZHANG Xin- (International Journal of Economics, Business and Management Studies, 2020)
The purpose of this paper is to examine the relationship between equity concentration and equity-based executive compensation (EBEC), and the moderating role of female executives in such a relationship between the two. Multiple statistical methods including Multiple Linear Regression Based on OLS, Random Effect Regression Analysis, and One-period Lagged-Term Regression have been applied to analyze the data drawn from a research sample of non-financial A-share listed companies from 2010 to 2018, which consists of 22151 observations in China. Empirical results show that large shareholders of Chinese listed companies have negative attitudes towards the adoption of EBEC; besides, female executives not only improve the adoption of EBEC directly, but enhance the adoption of EBEC indirectly by mitigating the negative link between large shareholders and the adoption of EBEC in Chinese listed companies. The rich robustness tests and endogeneity tests have confirmed the findings. Moreover, large shareholders intend to limit the cash compensation level of top executives, while female executives can not only directly improve top executives’ cash compensation level by participating in the compensation setting process, but also indirectly increase top executives’ cash compensation level by mitigating the negative attitudes of large shareholders towards executives’ cash compensation.